La cottura sub testu ai tempi dei romani: testa e clibani dalla Valle del Tevere. Il caso di Spoletino (Civitella d’Agliano - VT) - Elefante, Mara (Rei Cretariae Romanae Fautorum Acta, 2023)
Testa and clibani are the most common types of ceramic vessels used for baking during the Roman period, especially in Italy. They are a symbol of the kitchen and, at the same time, of rural pottery production, since they were produced mainly locally. The Roman cistern of Spoletino (Civitella d’Agliano-VT), filled in two different moments (mid-1st century AD and early 4th century AD) with a large amount of Roman pottery and other finds probably from a nearby villa, has brought to light a picture of daily life, especially for the aspects concerning the kitchen. Different testa and clibani were found, and they can help to define a precise chronology for these forms in the Tiber Valley area, but also more generally because of the substantial standardization. United with the production and the use study, the chronology provides a good picture of an aspect not always well explored that is baking in different moments of a Roman villa.